GOOGLE CLASSROOM ON STUDENTS’ WRITING LEARNING PROCESS - Janah, Miftahul; Yuniarti, Fatma (STKIP Muhammadiyah Pringsewu, 2019)
This study is Mix-Method Research applying exploratory design which aims to 1) know that the use of Google Classroom in Writing learning process can arouse students? learning interest and motivation; 2) know that Google Classroom can be used to improve student?s writing ability. The participants were the forth semester students of STKIP Muhammadiyah Pringsewu Lampung in academic year 2018/2019. Questionnaire, documentation, and test had been used to collect the data which was then analyzed using phased qualitative?quantitative analysis. The result showed that Google Classroom could encourage students to write, and help them to improve their writing ability. Keywords: Google Classroom, Writing Learning Process.